(untitled) (Heritage, 2020)
The subject of the paper is a list and analysis of Turkish words in the novel Testament. Their frequency will be observed, and the origin of the extracted examples will be revealed. The analysis will be carried out on the basis of Škalić’s dictionary "Turkish words in Serbo-Croatian language". The extracted lexemes are presented in their basic form, and are sorted first on the basis of morphological criteria and then on the semantic criteria. Aside from this type of sorting, a list of Turkish words from the novel will be listed in the form of a dictionary, and the context in which the word was used in the novel will be given. This kind of perception is necessary in order to obtain the fullest possible insight into the presence of Turkish words in the novel.